A global research synthesis of HIV and STI biobehavioural risks in female-to-male transgender adults. Issue 7 (13th September 2016) - Reisner, Sari L.; Murchison, Gabriel R.
ABSTRACT: There is a growing interest in HIV infection and sexually transmitted infection (STI) disease burden and risk among transgender people globally; however, the majority of work has been conducted with male-to-female transgender populations. This research synthesis comprehensively reviews HIV and STI research in female-to-male (FTM) transgender adults. A paucity of research exists about HIV and STIs in FTMs. Only 25 peer-reviewed papers (18 quantitative, 7 qualitative) and 11 'grey literature' reports were identified, most in the US or Canada, that include data identifying HIV and STI risks in FTMs (five with fully laboratory-confirmed HIV and/or STIs, and five with partial laboratory confirmation). Little is known about the sexual and drug use risk behaviours contributing to HIV and STIs in FTMs. Future directions are suggested, including the need for routine surveillance and monitoring of HIV and STIs globally by transgender identity, more standardised sexual risk assessment measures, targeted data collection in lower- and middle-income countries, and explicit consideration of the rationale for inclusion/exclusion of FTMs in category-based prevention approaches with MSM and transgender people. Implications for research, policy, programming, and interventions are discussed, including the need to address diverse sexual identities, attractions, and behaviours and engage local FTM communities.